Changes in scaffold porosity during bone tissue engineering in perfusion bioreactors considerably affect cellular mechanical stimulation for mineralization - Zhao, Feihu (Bone Rep, 2020)
Bone tissue engineering (BTE) experiments in vitro have shown that fluid-induced wall shear stress (WSS) can stimulate cells to produce mineralized extracellular matrix (ECM). The application of WSS on seeded cells can be achieved through bioreactors that perfuse medium through porous scaffolds. In BTE experiments in vitro, commonly a constant flow rate is used. Previous studies have found that tissue growth within the scaffold will result in an increase of the WSS over time. To keep the WSS in a reported optimal range of 10–30 mPa, the applied external flow rate can be decreased over time. To investigate what reduction of the external flow rate during culturing is needed to keep the WSS in the optimal range, we here conducted a computational study, which simulated the formation of ECM, and in which we investigated the effect of constant fluid flow and different fluid flow reduction scenarios on the WSS. It was found that for both constant and reduced fluid flow scenarios, the WSS did not exceed a critical value, which was set to 60 mPa. However, the constant flow velocity resulted in a reduction of the cell/ECM surface being exposed to a WSS in the optimal range from 50% at the start of culture to 18.6% at day 21. Reducing the fluid flow over time could avoid much of this effect, leaving the WSS in the optimal range for 40.9% of the surface at 21 days. Therefore, for achieving more mineralized tissue, the conventional manner of loading the perfusion bioreactors (i.e. constant flow rate/velocity) should be changed to a decreasing flow over time in BTE experiments. This study provides an in silico tool for finding the best fluid flow reduction strategy.